Polymorphisms in the inflammatory pathway genes TLR2, TLR4, TLR9, LY96, NFKBIA, NFKB1, TNFA, TNFRSF1A, IL6R, IL10, IL23R, PTPN22, and PPARG are associated with susceptibility of inflammatory bowel disease in a Danish cohort. - Steffen Bank; Paal Skytt Andersen; Johan Burisch; Natalia Pedersen; Stine Roug; Julie Galsgaard; Stine Ydegaard Turino; Jacob Broder Brodersen; Shaista Rashid; Britt Kaiser Rasmussen; Sara Avlund; Thomas Bastholm Olesen; et al. (PLoS ONE)
Background The inflammatory bowel diseases (IBD), Crohn's disease (CD) and ulcerative colitis (UC), result from the combined effects of susceptibility genes and environmental factors. Polymorphisms in genes regulating inflammation may explain part of the genetic heritage. Methods Using a candidate gene approach, 39 mainly functional single nucleotide polymorphisms (SNPs) in 26 genes regulating inflammation were assessed in a clinical homogeneous group of severely diseased patients consisting of 624 patients with CD, 411 patients with UC and 795 controls. The results were analysed using logistic regression. Results Sixteen polymorphisms in 13 genes involved in regulation of inflammation were associated with risk of CD and/or UC (p ≤ 0.05). The polymorphisms TLR2 (rs1816702), NFKB1 (rs28362491), TNFRSF1A (rs4149570), IL6R (rs4537545), IL23R (rs11209026) and PTPN22 (rs2476601) were associated with risk of CD and the polymorphisms TLR2 (rs1816702), TLR4 (rs1554973 and rs12377632), TLR9 (rs352139), LY96 (rs11465996), NFKBIA (rs696), TNFA (rs1800629), TNFRSF1A (rs4149570), IL10 (rs3024505), IL23R (rs11209026), PTPN22 (rs2476601) and PPARG (rs1801282) were associated with risk of UC. When including all patients (IBD) the polymorphisms TLR2 (rs4696480 and rs1816702), TLR4 (rs1554973 and rs12377632), TLR9 (rs187084), TNFRSF1A (rs4149570), IL6R (rs4537545), IL10 (rs3024505), IL23R (rs11209026) and PTPN22 (rs2476601) were associated with risk. After Bonferroni correction for multiple testing, both the homozygous and the heterozygous variant genotypes of IL23R G>A(rs11209026) (OR(CD,adj): 0.38, 95% CI: 0.21-0.67, p = 0.03; OR(IBD,adj) 0.43, 95% CI: 0.28-0.67, p = 0.007) and PTPN22 1858 G>A(rs2476601) (OR(CD,unadj) 0.54, 95% CI: 0.41-0.72, p = 7*10-4; OR(IBD,unadj): 0.61, 95% CI: 0.48-0.77, p = 0.001) were associated with reduced risk of CD. Conclusion The biological effects of the studied polymorphisms suggest that genetically determined high inflammatory response was associated with increased risk of CD. The many SNPs found in TLRs suggest that the host microbial composition or environmental factors in the gut are involved in risk of IBD in genetically susceptible individuals.